Skip to main content
Solve for a
Tick mark Image
Solve for d
Tick mark Image

Similar Problems from Web Search

Share

m\left(2a+\left(m-1\right)d\right)=n\left(2a+\left(n-1\right)d\right)
Multiply both sides of the equation by 2.
m\left(2a+md-d\right)=n\left(2a+\left(n-1\right)d\right)
Use the distributive property to multiply m-1 by d.
2ma+dm^{2}-md=n\left(2a+\left(n-1\right)d\right)
Use the distributive property to multiply m by 2a+md-d.
2ma+dm^{2}-md=n\left(2a+nd-d\right)
Use the distributive property to multiply n-1 by d.
2ma+dm^{2}-md=2na+dn^{2}-nd
Use the distributive property to multiply n by 2a+nd-d.
2ma+dm^{2}-md-2na=dn^{2}-nd
Subtract 2na from both sides.
2ma-md-2na=dn^{2}-nd-dm^{2}
Subtract dm^{2} from both sides.
2ma-2na=dn^{2}-nd-dm^{2}+md
Add md to both sides.
2am-2an=-dm^{2}+dm+dn^{2}-dn
Reorder the terms.
\left(2m-2n\right)a=-dm^{2}+dm+dn^{2}-dn
Combine all terms containing a.
\frac{\left(2m-2n\right)a}{2m-2n}=\frac{d\left(n-m\right)\left(m+n-1\right)}{2m-2n}
Divide both sides by 2m-2n.
a=\frac{d\left(n-m\right)\left(m+n-1\right)}{2m-2n}
Dividing by 2m-2n undoes the multiplication by 2m-2n.
a=-\frac{d\left(m+n-1\right)}{2}
Divide d\left(-1+m+n\right)\left(-m+n\right) by 2m-2n.
m\left(2a+\left(m-1\right)d\right)=n\left(2a+\left(n-1\right)d\right)
Multiply both sides of the equation by 2.
m\left(2a+md-d\right)=n\left(2a+\left(n-1\right)d\right)
Use the distributive property to multiply m-1 by d.
2ma+dm^{2}-md=n\left(2a+\left(n-1\right)d\right)
Use the distributive property to multiply m by 2a+md-d.
2ma+dm^{2}-md=n\left(2a+nd-d\right)
Use the distributive property to multiply n-1 by d.
2ma+dm^{2}-md=2na+dn^{2}-nd
Use the distributive property to multiply n by 2a+nd-d.
2ma+dm^{2}-md-dn^{2}=2na-nd
Subtract dn^{2} from both sides.
2ma+dm^{2}-md-dn^{2}+nd=2na
Add nd to both sides.
dm^{2}-md-dn^{2}+nd=2na-2ma
Subtract 2ma from both sides.
\left(m^{2}-m-n^{2}+n\right)d=2na-2ma
Combine all terms containing d.
\left(m^{2}-m-n^{2}+n\right)d=2an-2am
The equation is in standard form.
\frac{\left(m^{2}-m-n^{2}+n\right)d}{m^{2}-m-n^{2}+n}=\frac{2a\left(n-m\right)}{m^{2}-m-n^{2}+n}
Divide both sides by m^{2}-m-n^{2}+n.
d=\frac{2a\left(n-m\right)}{m^{2}-m-n^{2}+n}
Dividing by m^{2}-m-n^{2}+n undoes the multiplication by m^{2}-m-n^{2}+n.
d=-\frac{2a}{m+n-1}
Divide 2a\left(n-m\right) by m^{2}-m-n^{2}+n.